1998
DOI: 10.1128/aem.64.3.1040-1044.1998
|View full text |Cite
|
Sign up to set email alerts
|

A Fermentor System for Regulating Oxygen at Low Concentrations in Cultures of Saccharomyces cerevisiae

Abstract: The growth of yeast cells to high densities at low, but constant, oxygen concentrations is difficult because the cells themselves respire oxygen; hence, as cell mass increases, so does oxygen consumption. To circumvent this problem, we have designed a system consisting of a computer-controlled gas flow train that adjusts oxygen concentration in the gas flow to match cellular demand. It does this by using a proportional-integral-differential algorithm in conjunction with a three-way valve to mix two gases, adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The S. cerevisiae strain JM43 ( MATα leu2-3,112 his4-580 trp1-289 ura3-52 [ρ +] )[ 50 ] was used. Liquid pre-cultures were grown in a semi-synthetic galactose medium containing Tween 80, ergosterol, and silicon antifoam (SSG-TEA) [ 51 ] with shaking (300 rpm) for 3 – 4 days prior to inoculating a NewBrunswick BioFlo III fermentor (3.5 l working volume) [ 52 ]. Batch fermentor cultures were inoculated with a volume of pre-culture to allow for at least six generations of aerobic growth before reaching a cell density of ≈ 1 Klett unit.…”
Section: Methodsmentioning
confidence: 99%
“…The S. cerevisiae strain JM43 ( MATα leu2-3,112 his4-580 trp1-289 ura3-52 [ρ +] )[ 50 ] was used. Liquid pre-cultures were grown in a semi-synthetic galactose medium containing Tween 80, ergosterol, and silicon antifoam (SSG-TEA) [ 51 ] with shaking (300 rpm) for 3 – 4 days prior to inoculating a NewBrunswick BioFlo III fermentor (3.5 l working volume) [ 52 ]. Batch fermentor cultures were inoculated with a volume of pre-culture to allow for at least six generations of aerobic growth before reaching a cell density of ≈ 1 Klett unit.…”
Section: Methodsmentioning
confidence: 99%
“…The three PLS models developed in the current study indicated that the H/D of the bioreactor and PID control of dissolved oxygen concentration had a significant impact on the production of biomass, cyt b5, and respective production yield. In fermenters, regulation of dissolved oxygen concentration may be fine-tuned by a PID algorithm, especially when oxygen supply is controlled by stirring speed [ 53 , 54 ]. Adjustment of the three parameters may improve the regulation for low oxygen concentrations [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…7B , cells were grown in YEP media supplemented with 2% dextrose or 4% galactose. In the case of the nitrogen shift experiments, assays were performed using cells grown in 600 ml of semisynthetic medium (SSD) containing per liter, 3 g of yeast extract, 10 g of dextrose, 0.8 g of NH 4 SO 4 , 1 g of KH 2 PO 4 , 0.5 g of NaCl, 0.5 g of CaCl 2 •2H 2 O, 0.3 g of MgSO 4 , 1.1 μg of FeCl 3 •6H 2 O, supplemented with amino acids, adenine and uracil at 40 μg/ml, 0.1% (V/V) Tween 80, 20 μg/ml of ergosterol and 350 ppm of antifoam B emulsion (Sigma-Aldrich, St. Louis, MO) [ 63 ] using Multifors (Infors Canada, Anjou, QC, Canada) bioreactors. Cells were grown to 0.3 OD 600 in air-supplemented media than the gas supply was shifted to nitrogen.…”
Section: Methodsmentioning
confidence: 99%